Mechanism of stable lithium plating and stripping in a metal-interlayer-inserted anode-less solid-state lithium metal battery - Dong-Su Ko; Sewon Kim; Sangjun Lee; Gabin Yoon; Daeho Kim; ChaeHo Shin; Dongmin Kim; Jaewoo Lee; Soohwan Sul; Dong-Jin Yun; Changhoon Jung (Nature Communications, 2025)
Abstract To reliably operate anode-less solid-state Li metal batteries, wherein precipitated Li acts as the anode, stabilizing the interface between the solid electrolyte and electrode is crucial. The interface can be controlled by a metal interlayer on the electrolyte to form a Li alloy buffer that facilitates stable Li plating/stripping, thereby mitigating the loss of physical contact and preventing short circuits. However, the mechanism governing stable Li plating/stripping in the metal interlayer without degrading battery materials remains unclear owing to an incomplete understanding of the dynamic and complex electrochemical reactions in the solid state. Through multiple operando and post-mortem analyses of the Li deposition behavior in the morphology, chemistry and microstructure, a close correlation is found between the Li-metal alloying process with the microstructural evolution and electrochemical performance when Ag, Au, Zn, and Cu interlayers were adopted on the garnet-type solid electrolyte Li6.5La3Zr1.5Ta0.5O12. The Ag interlayer improved the interfacial stability enabled by Ag-dissolved Li, which inhibited dendritic growth, passing through the phase-separated Li-Ag alloy microstructure, while the other metals did not because of the Li plating at the Li-metal alloy/solid electrolyte interface. This work provides fundamental guidance for material selection and interface design, advancing the development of anode-less solid-state batteries.